The Effect of Jigsaw Method to Improve EFL Students’ Vocabulary Ability - Hesni Neno; Yohanes Paulus Florianus Erfiani (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2018)
This study was aimed to improve students’ ability in learning vocabulary through jigsaw method at Timor University in, Timor Tengah Utara regency (TTU), NTT Province, Indonesia. The main purpose of this study is to know the effect of using jigsaw method to improve students’ vocabulary ability. This study belongs to pre experimental method with the one group pretest - posttest design. This study was conducted in one class which was given the treatment. The treatment of this study is teaching and learning process by using jigsaw method. The population of this study was second semester students of English study program of Timor university in academic year 2017 / 2018. The total members of second semester students were 120 who were divided into three (3) classes. Every class consisted of 30 students. The writers used purposive sampling technique to take the data. The writers only determined one class because the writer assumed that in this class, students have sufficient knowledge of English. Hence, the sample of this study was 30 students. The writers had conducted pre test before gave the treatment to the students. Finally, the writers gave the posttest to measure students’ vocabulary ability in the end of teaching and learning process. From the data analysis, the writers found that the average of the students’ vocabulary was improvement. The average of students’ score in pretest was 65% and posttest was 79%. After the writers conducted the research, the writers concluded that (1). Jigsaw method can improve students’ vocabulary ability. (2). Jigsaw method can improve the students’ interaction with the teacher and other students.